Simulation study on ranging by FMCW radar - Soe, Min Oo. (2013)
Nowadays, radars are deployed not only for military purposes but also for civilian applications. Most of the radars found in individual usages are especially dedicated for vehicle collision avoidance systems. Their common purposes are to detect ranges and velocities of other vehicles; nearby, oncoming, receding or passing by. And, to alert a driver about any possible collisions is its primary purpose. Then, the driver has to take any necessary measures. This type of radars can mostly be found in the form of FMCW (Frequency-Modulated Continuous-wave) application because of its advantages over pulsed radars in this field of utility.